2021
DOI: 10.1002/hep.31802
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, MicroRNA‐122 Gene‐Regulation, and Protective Immune Responses After Acute Equine Hepacivirus Infection

Abstract: Equine hepacivirus (EqHV); hepatitis C virus (HCV); GB-virus B (GBV-B); non-primate hepacivirus, NPHV; untranslated region (UTR); peripheral blood mononuclear cell (PBMC); interferon (IFN); genome equivalents (GE); RNA-sequencing (RNA-seq); single cell RNA-sequencing (scRNA-seq); luciferase immunoprecipitation system (LIPS); equine pegivirus (EPgV); Theiler's disease associated virus (TDAV); human pegivirus (HPgV/GBV-C); differentially expressed (DE); IFN-stimulated genes (ISGs); rodent hepacivirus (RHV); simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…Information about RNA extraction and library preparation [ 5 ] has been included in the Supplementary material . Differential gene analysis was performed in R, as described previously [ 6 ]. Briefly, we used the Limma-voom and DeSeq2 package for preprocessing and principal component (PC) analysis, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Information about RNA extraction and library preparation [ 5 ] has been included in the Supplementary material . Differential gene analysis was performed in R, as described previously [ 6 ]. Briefly, we used the Limma-voom and DeSeq2 package for preprocessing and principal component (PC) analysis, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of strong selection pressure and the low diversity could be linked to a weak humoral immune response which has previously been observed in EqHV-infected horses ( Pfaender et al. 2017 ; Tomlinson et al. 2021 ).…”
Section: Discussionmentioning
confidence: 70%
“…2015 ; Pfaender et al. 2017 ; Tomlinson et al. 2021 ), however, it was shown that foals infected with EqHV remained RNA positive for at least a year post-infection, indicating that persistent EqHV infection can be achieved by experimental inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because it relies on direct sequencing as compared to the use of predefined probes in microarrays, it is suitable for the detection of novel genes or transcripts of interest that may not be represented on the microarray chip. Third, the direct sequencing approach makes RNA-seq highly suitable for use in surrogate animal models of different species such as the equine hepacivirus (EqHV) model [ 25 ]. Finally, RNA-seq data provide additional analysis opportunities for important biological information, e.g., the comparison of differential splicing across samples [ 26 , 27 ], functionally relevant single nucleotide polymorphism (SNP) analysis [ 28 ] and RNA editing events [ 29 , 30 , 31 ].…”
Section: Overview and Comparison Of Systems-transcriptomic Methodsmentioning
confidence: 99%
“…Comparative analyses demonstrated common signatures with those of flaviviruses yellow fever and dengue [ 53 ]. Recent RNA-seq analysis of the liver and peripheral blood of horses infected with equine hepacivirus (EqHV), which is highly related to HCV, demonstrated an ISG signature in the liver [ 25 ]. However, only minimal perturbations in adaptive immune cell signatures were detectable in the peripheral blood despite the fact that EqHV-specific T cells were identified following specific peptide stimulation [ 25 ].…”
Section: Systems Biology Studies Of the Immune Response During Acute And Chronic Hcv Infectionmentioning
confidence: 99%